Cirrhotic liver: What's that nodule? The LI‐RADS approach. Issue 2 (21st May 2015) - Shah, Amol; Tang, An; Santillan, Cynthia; Sirlin, Claude
Abstract : The Liver Imaging Reporting and Data System (LI‐RADS) is an American College of Radiology (ACR)‐endorsed diagnostic system of standardized terminology, interpretation, and reporting for imaging examinations of the liver in patients at high risk for hepatocellular carcinoma (HCC). LI‐RADS assigns a category to observations in the liver indicating the likelihood of benignity or HCC. LI‐RADS categories include LR‐1: Definitely Benign, LR‐2: Probably Benign, LR‐3: Intermediate Probability for HCC, LR‐4: Probably HCC, LR‐5: Definite HCC, LR‐5V: Definite HCC with Tumor in Vein, LR‐Treated: Treated HCC, LR‐M Probable Malignancy, not specific for HCC. This article reviews the types of nodules seen in the cirrhotic liver, examines core LI‐RADS concepts and definitions, and utilizes the LI‐RADS v2014 algorithm to categorize representative observations depicted at magnetic resonance imaging in a case‐based approach. J. Magn. Reson. Imaging 2016;43:281–294.